2018
DOI: 10.15611/aoe.2018.2.10
|View full text |Cite
|
Sign up to set email alerts
|

IPO underpricing phenomenon on the karachi stock exchange

Abstract: In this study the risk-adjusted performance of IPO firms listed on the KSE from 2000 to 2012 is analyzed. The objective is to provide insights of the underpricing (first trading day) of IPOs and to find out the determinants of underpricing in the light of asymmetric information and signaling theories. The results indicate that underpricing prevails on the KSE. The level of underpricing with regard to the marked adjusted model is found to be 28.28 percent for the full sample of 83 IPOs, which shows that investo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
1
2
1
Order By: Relevance
“…This finding is consistent to Hermin and Murhadi (2015), Malhotra and Nair (2015) and Subedi and Dangal (2022) which implies size of company is not noticed by investors during investment in IPOs. Result of this study on firm size contradicts the findings of Kristiantari (2013), Sohail et al (2018) and Ferdous et al (2021) studies that found negative significant relationship between firm size and level of underpricing.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent to Hermin and Murhadi (2015), Malhotra and Nair (2015) and Subedi and Dangal (2022) which implies size of company is not noticed by investors during investment in IPOs. Result of this study on firm size contradicts the findings of Kristiantari (2013), Sohail et al (2018) and Ferdous et al (2021) studies that found negative significant relationship between firm size and level of underpricing.…”
Section: Discussioncontrasting
confidence: 99%
“…This indicates investors overreact to IPOs and their overreaction explains level of underpricing for a longer length of time. This finding is consistent with study of Malhotra and Nair (2015), Pradhan and Shrestha (2016), Sohail et al (2018) and Subedi and Dangal (2022) that shows significant positive relationship between subscription rate and level of underpricing that expounds that the higher the extent of over subscription will lead to shortage in investors allocation so investors tend to overpay for share in order to fulfill their desired allocation. Uninformed investors also tend to follow the informed investors and results higher subscription rate for shares, thus resulting underperformance for longer duration.…”
Section: Discussionsupporting
confidence: 91%
“…High initial returns can be described as the direct transfer of wealth to outside shareholders (or new investors) from the perspective of the existing shareholders or original owners (Bédard et al , 2008). Notably, high IPO initial returns are the most recurring phenomenon found in every financial market, including in the US (Lowry et al , 2010), France and Germany (Goergen et al , 2009), the United Kingdom (UK) (Reber and Fong, 2006), New Zealand (NZ) (Chi et al , 2010), Poland (Sieradzki, 2013), Brazil (Nogueira Freitas et al , 2008), Sri Lanka (Samarakoon, 2010), Thailand (Vithessonthi, 2014), Malaysia (Che-Yahya et al , 2018) and Pakistan (Aslam and Ullah, 2017; Javid and Malik, 2016; Sohail et al , 2018b). In the context of Pakistan, Aslam and Ullah (2017) reported an average initial return of 46.00%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…High IPO initial returns have been proven in all financial markets worldwide (Lowry et al, 2017;Mohd-Rashid et al, 2018). Persistent anomalies of high initial returns have also been reported in Pakistan's financial market (Aslamand Ullah, 2017;Khalid and Farhat, 2018;Sohail et al, 2018b). Nevertheless, the intensity of IPO initial return and its determinants differ amongst countries due to reasons such as listing regulation, the involvement of underwriters, government intervention, economic condition and methodological issues (Khan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%